Hemimyzon luae, a new species of balitorid fish (Teleostei: Baltioridae) from the Tzengwen River basin, southern Taiwan - Chen, I-Shiung; Yeh, Ming-Fon (Zootaxa, 2024)
The new balitorid fish was collected in the Tzengwen river basin from southern Taiwan. The new species, Hemimyzon luae n. sp. can be well distinguished from other congeneric species by following combination of features: (1) dorsal fin rays 3 + 8; pectoral fin rays 11–12 + 9–11 (total 20–22; modally 22); (2) pelvic fin moderate large, extending to rear vertical of dorsal fin, pelvic simple rays modally 3 which fewer than any other endemic ones of Taiwan; (3) lateral-line scales 68–72 (modally 70); predorsal scales 39–42 (modally 40); (4) the position of anus with much larger distance of pelvic rear tip to anus about 2.4–3.2 times of that of anus to anal fin origin and (5) specific coloration: dorsum of body and head olive brown to greenish brown; predrorsal region deep brown with several rounded or oblong cloudy deep brown patches; lateral body uniformly olive brown to deep brown; and pectoral, pelvic and anal fins pale white with deep brown rays. The morphological comparison of congeners and the diagnostic key of Taiwanese species would be also provided in this paper.